Respuestas
Respuesta dada por:
8
Respuesta:
senA = y/r = 4/5
cosA = x/r = -3/5
tgA = y/x = 4/-3 = -4/3
ctgA = x/y = -3/4
secA = r/x = 5/-3 = -5/3
cscA = r/y = 5/4
Explicación paso a paso:
Sea "A" el ángulo.
P(-3; 3)
x = -3
y = 4
r = ?
r = \sqrt{ {x}^{2} + {y}^{2} }r=x2+y2
r = \sqrt{ {( - 3)}^{2} + {(4)}^{2} }r=(−3)2+(4)2
r = \sqrt{9 + 16}r=9+16
r = \sqrt{25}r=25
r = 5r=5
Finalmente:
senA = y/r = 4/5
cosA = x/r = -3/5
tgA = y/x = 4/-3 = -4/3
ctgA = x/y = -3/4
secA = r/x = 5/-3 = -5/3
cscA = r/y = 5/4
Preguntas similares
hace 4 años
hace 4 años
hace 4 años
hace 7 años
hace 8 años